Determinants and performance of cash holding: evidence from small business in Malaysia - Mohd Ashhari, Zariyawati; Faizal, Diana Rose (Kulliyyah of Economics and Management Sciences, International Islamic University, 2018)
Cash holding plays an important role in a business to ensure smooth operations. It is not only vital in the daily operation of a large firm but also in small firms such as a private firm or small and medium enterprise (SME). However, the manager puts less concern on the function of cash holding in small business. The purpose of this study is to investigate the effect of cash holding on small business performance in Malaysia. One hundred SMEs constituted the sample; panel data with robust standard errors were examined from 2011 to 2016. The findings indicate a significant relationship between cash holding and small business performance. We also investigate the determinant of cash holding in small business. Our results show that leverage, growth opportunity, firm size, cash flow volatility, capital expenditure and net working capital are determinant factors of cash holding in small business. Thus, this study can be directly contributed to SMEs and policy maker related on SMEs sector about the specific view of the cash holding in small firms in Malaysia.